Methods of integration: combining archaeological and paleoenvironmental datasets within a GIS framework - Bonnier , Anton (Journal of Greek Archaeology, 2024)
Within Mediterranean archaeology there has been a growing interest in exploring various aspects of human-environment interactions. This research has highlighted how societal dynamics can be understood in light of environmental transformation. The increasing scholarly interest in such questions – in what is sometimes defined as the environmental turn in archaeology – can to a certain extent be linked with our own contemporary environmental concerns. Archaeological research may provide new perspectives on long term patterns of human-environment interactions and can therefore serve as an important tool for policy making in the present.